PENGEMBANGAN KUALITAS DAN MANAJEMEN SUMBER DAYA MANUSIA PADA BANK SYARIAH - Anisa Muslima; husnul khotimah sylvia; Uswatun Hasanah (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
Bank syariah di Indonesia terus mengalami pertumbuhan baik dari sisi aset, jumlah kantor, jumlah nasabah, dan pangsa Islamic banking in Indonesia continues to experience growth both in terms of assets, the account of offices, the account of costumers, and the market share of islamic banking that exceed 5%. The growth of islamic banking is not followed by adequate human resources both in quantity and quality. Human resources are still a difficult problem for islamic banking now. In the roadmap of islamic banking period 2015-2019 issued to make the Financial Service Authoritz to make human resource issues into things to be resolved. It takes a pattern of human resource management that can create qualified human resources for islamic banking. This paper is qualitative descriptive that will describe the growth of human resources in islamic banking, as well as the important role of Islamic human resource management for human resource in islamic banking. This paper shows the growth of humanresources in islamic banking in the period of December 2016 until Setember 2017 grew bz 2.368%, with the totalhuman resources of islamic banking today as much as 61,389 people. The pattern of Islamic human resource management becomes important for the availability of best quality of human resources in Islamic banking human resource management able to meet the human resource who understand the science of economics and science of Islamic human resource management covers the entire process of establishing human resource in islamic banking. One of the patterns of Islamic human resource management that is relevant to the current state of islamic banking is Calestial Management. It consist of ZIKR, PIKR and MIKR.pasar bank syariah yang telah melebihi 5%. Pertumbuhan bank syariah tidak diikuti dengan sumber daya manusia yang memadai baik secara kuantitas dan kualitas. Sumber daya manusia masih menjadi maslah yang sulit bagi bank syariah. Pada roadmap perbankan syariah 2015-2019 ang dikeluarkan menjadi Otoritas Jasa Keuangan (OJK) menjadi masalah sumber daya manusia menjadi hal yang harus diselesaikan. Dibutuhkan sebuah pola manajemen sumber daya manusia yang bisa menciptakan SDM yang berkualitas bagi bank syariah. Tulisan ini bersifat kualitatif deskriptif yang akan menguraikan pertumbuhan SDM di bank syariah, serta peran penting manajemen sumber daya manusia islam bagi SDM di bank syariah. Tulisan ini menunjukan adanya pertumbuhan SDM di bank syariah pada periode Desember 2016 sampai September 2017 mengalami pertumbuhan sebesar 2,368%, dengan total SDM bank syariah saat ini sebanyak 61.389 orang. Manajemen sumber daya manusia islami menjadi penting bagi tersedianya SDM bank syariah yang berkualitas baik. Manajemen sumber daya manusia islami mampu memenuhi SDM yang paham akan ilmu ekonomi dan ilmu syariah. Manajemen sumber daya manusia islam meliputi pembentukan SDM di bank syariah. Salah satu pola manajemen sumber daya manusia islam yang relevan dengan kondisi SDM bank syariah saat ini yaitu Calestial Management. Yang terdiri dari ZIKIR, PIKR, dan MIKR.